2008
DOI: 10.1002/anie.200704700
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Asymmetric Fluorination Comes of Age

Abstract: asymmetric catalysis · electrophilic substitution · fluorinated substituents · fluorinationThe CÀF bond is a fundamental unit of organic chemistry, and its introduction into organic compounds has been widely deployed to optimize the properties of performance materials.[1] Important contemporary applications are in organic materials such as liquid crystals for display technologies, [2] the refinement of catalysts for asymmetric transformations, [3] as well as the important role of strategic fluorination for lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
33
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 180 publications
(33 citation statements)
references
References 34 publications
0
33
0
Order By: Relevance
“…Planar tridentate NNN ligands have recently been paid much attention due to their potential applications in homogeneous catalysis, organic synthesis, materials and physical chemistry [13][14][15]. However, examples of unsymmetrical planar tridentate NNN ligands and their transition metal complexes have only been scattered [16][17][18][19][20]. Recently, we found that phosphinefree unsymmetrical pyridyl-supported 2,6-(mixed N-heterocycles) ligands can demonstrate a dynamic ''on and off" chelating effect for the metal center during catalysis, and their transition metal complexes usually exhibit enhanced catalytic activity and selectivity [21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Planar tridentate NNN ligands have recently been paid much attention due to their potential applications in homogeneous catalysis, organic synthesis, materials and physical chemistry [13][14][15]. However, examples of unsymmetrical planar tridentate NNN ligands and their transition metal complexes have only been scattered [16][17][18][19][20]. Recently, we found that phosphinefree unsymmetrical pyridyl-supported 2,6-(mixed N-heterocycles) ligands can demonstrate a dynamic ''on and off" chelating effect for the metal center during catalysis, and their transition metal complexes usually exhibit enhanced catalytic activity and selectivity [21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…1,2 The incorporation of fluorine can improve the pharmacokinetic properties of lead molecules, as it is known to increase metabolic stability and lipophilicity. Although there are many methods to introduce fluorine 3 and trifluoromethyl groups, 4 there are substantially fewer strategies to install a difluoromethylene group. 57 The most common synthetic protocols for installing a difluoromethylene group are through the use of a difluoroenol 8 or a difluoroenolate.…”
mentioning
confidence: 99%
“…Recently reported general methods for the enantioselective synthesis of allylic fluorides include the reaction of allylic chlorides with palladium catalysts (24,25) as well as the fluorination of allylsilanes using cinchona alkaloid catalysis (26,27). Furthermore, we envisioned that, upon removal of the amide directing group, this method would provide access to enantioenriched β-fluoroamines bearing a fluorinated quaternary center, a privileged bioactive motif and longstanding synthetic challenge (28)(29)(30)(31)(32)(33).…”
mentioning
confidence: 99%